Socioscientific-Issues Based Classroom Intervention on Grade 10 Students’ Learning Achievement and Scientific Reasoning - Linda Khajornkhae,; Prasart Nuangchalerm, (Journal of Educational Issues, 2024)
Socioscientific-issues based instruction can promote science to students as a tool for necessary learning in the disruptive world. This instruction helps students critique and response as its nature of science, gaining higher-ordered thinking, and discussing with scientific reasoning. The objectives of this study were to compare learning achievement and scientific reasoning of grade 10 students. The topic “DNA technology” was employed with 90 grade 10 students from 2 classrooms. The quasi-experimental research was designed by comparing learning achievement and scientific reasoning between 2 learning organizations. The research tools were socioscientific-issues based and inquiry-based lesson plans, the achievement test consist of 30 items of 4 choices multiple test and scientific reasoning test. The statistic used to test the hypothesis was independent t-test. The results indicated that students had no difference score of learning achievement between learning organizations. While socioscientific-issues based learning had score of scientific reasoning higher than inquiry-based learning at the .05 level of statistically significance. The study can summarize that socioscientific-issues based learning can promote scientific reasoning to science classroom.